Molecular detection, risk factors and public awareness of avian bornavirus among captive and non-captive birds in Peninsular Malaysia - Mohd Lutpi, Syamsiah; Abu, Jalila; Arshad, Siti Suri; Rahaman, Nor Yasmin (Sciendo, 2022)
Introduction: Proventricular dilatation disease (PDD) is caused by avian bornavirus (ABV) has been identified in psittacine, non-psittacine birds and waterfowl. Birds may show signs of gastrointestinal tract deficit or neurological dysfunction or even both. The objectives of this study were to determine the molecular prevalence, risk factors and public awareness of ABV and PDD among captive and non-captive birds in Peninsular Malaysia. Material and Methods: A total of 344 cloacal swabs or faeces were collected and subjected to detection using the RT-PCR assay. Meanwhile, KAP questionnaires were distributed by using the Google forms platform. Results: Molecular prevalence studies revealed that 4.5% (9/201) of the pet birds were ABV-positive, whereas 0% (0/143) in waterfowl. Nine positive pet birds were identified to be PaBV-2, which is closest to ABV isolates EU781967 (USA). Among the risk factors analysed, category, age and, location, were found to show an association with the ABV positivity. The KAP survey result showed: the respondents have low knowledge (32.9%), however, they showed positive attitude (60.8%) and good practice (94.9%). The association between knowledge, attitude and practice showed that there was a significant association between knowledge-attitude and also attitude-practice (P < 0.05). Conclusion: This study proved that avian bornavirus (ABV) causes proventricular dilatation disease (PDD) among a group of pet birds of Psittaciformes, but it is present in Peninsular Malaysia with a low prevalence rate. Furthermore, in addition to the useful databases obtained from this study, the level of public awareness on the importance of avian bornavirus that causes fatal disorders among a wide range of bird species is satisfactorily raised.